From Oral Hygiene to Cognitive Health: Examining the Relationship between Periodontal Disease and Alzheimer's - , Yann Nobre Viana; , Richelly Maria Rodrigues Holanda; , Matéus Simplício Araújo; , Francisco Cesar Barroso Barbosa (Archives of Current Research International, 2024)
Aim: The aim of this study was to review the literature in an integrative way, looking for scientific evidence to see if there is a relationship between periodontal disease (PD) and Alzheimer's disease (AD). Study Design: Review the literature in an integrative. Methodology: The search was carried out on the VHL Regional Portal with articles published in English, Spanish and Portuguese. 169 articles were found between 2021 and 2023. Of this total, 106 were excluded, 5 for being duplicates and 101 for not meeting the inclusion criteria. Of the studies analyzed, most report evidence of an association between PD and AD, with Phorphyromonas gingivalis (PG) as the common pathogen in both conditions. Results: The results revealed four aspects: a) PG and other periodontopathogens (PP) play a role in the systemic inflammation process that accelerates the onset and progression of AD; b) even given the link between the oral-brain aetiological axis hypothesis of a brain degeneration syndrome such as AD, it is still necessary to further investigate the role of PP and PG (multimicrobial hypothesis) in the pathogenesis and worsening of AD; c) PD represents a factor in the progression of AD via induced pathogenic bacteria, since these individuals may have poor oral hygiene care, due to forgetfulness or less manual dexterity; d) Age and gender are important variables to consider when assessing the association between PD and AD. Conclusion: Thus, we can infer that despite the number of studies observed through this integrative review, there is still not enough research with a high level of scientific evidence on this association. Thus, new studies with greater methodological rigor in terms of the methods applied and the criteria for diagnosing the pathologies need to be carried out in order to obtain a better understanding of the relationship between PD and AD.